Characterizing Microheterogeneity in Liquid Mixtures via Local Density Fluctuations - Lass, Michael; Kenter, Tobias; Plessl, Christian; Brehm, Martin (Entropy)
We present a novel approach to characterize and quantify microheterogeneity and microphase separation in computer simulations of complex liquid mixtures. Our post-processing method is based on local density fluctuations of the different constituents in sampling spheres of varying size. It can be easily applied to both molecular dynamics (MD) and Monte Carlo (MC) simulations, including periodic boundary conditions. Multidimensional correlation of the density distributions yields a clear picture of the domain formation due to the subtle balance of different interactions. We apply our approach to the example of force field molecular dynamics simulations of imidazolium-based ionic liquids with different side chain lengths at different temperatures, namely 1-ethyl-3-methylimidazolium chloride, 1-hexyl-3-methylimidazolium chloride, and 1-decyl-3-methylimidazolium chloride, which are known to form distinct liquid domains. We put the results into the context of existing microheterogeneity analyses and demonstrate the advantages and sensitivity of our novel method. Furthermore, we show how to estimate the configuration entropy from our analysis, and we investigate voids in the system. The analysis has been implemented into our program package TRAVIS and is thus available as free software.

Ultrafast Proton Transfer Pathways Mediated by Amphoteric Imidazole - Codescu, M.-A.; Kunze, T.; Weiß, M.; Brehm, Martin; Kornilov, O.; Sebastiani, D.; Nibbering, E. T. J. (J. Phys. Chem. Lett.)

A Force Field for Bio-Polymers in Ionic Liquids (BILFF) – Part 2: Cellulose in [EMIm][OAc] / Water Mixtures - Roos, E.; Sebastiani, D.; Brehm, Martin (Phys. Chem. Chem. Phys.)

Lactate-Based Ionic Liquids as Chiral Solvents for Cellulose - Radicke, J.; Roos, E.; Sebastiani, D.; Brehm, Martin; Kressler, J. (J. Polym. Sci.)

Second-harmonic generation in atomically thin 1T−TiSe2 and its possible origin from charge density wave transitions - Zhang, Ruiming; Ruan, Wei; Yu, Junyao; Gao, Libo; Berger, Helmuth; Forró, László; Watanabe, Kenji; Taniguchi, Takashi; Ranjbar, Ahmad; Belosludov, Rodion V.; Kühne, Thomas; Bahramy, Mohammad Saeed; et al. (Physical Review B)

Electronic Structures of Group III–V Element Haeckelite Compounds: A Novel Family of Semiconductors, Dirac Semimetals, and Topological Insulators - Khazaei, Mohammad; Ranjbar, Ahmad; Kang, Yoon‐Gu; Liang, Yunye; Khaledialidusti, Rasoul; Bae, Soungmin; Raebiger, Hannes; Wang, Vei; Han, Myung Joon; Mizoguchi, Hiroshi; Bahramy, Mohammad S.; Kühne, Thomas; et al. (Advanced Functional Materials)
Keywords: Electrochemistry; Condensed Matter Physics; Biomaterials; Electronic; Optical and Magnetic Materials

Real-Space Identification of Non-Noble Single Atomic Catalytic Sites within Metal-Coordinated Supramolecular Networks - Schulze Lammers, Bertram; López-Salas, Nieves; Stein Siena, Julya; Mirhosseini, Hossein; Yesilpinar, Damla; Heske, Julian Joachim; Kühne, Thomas; Fuchs, Harald; Antonietti, Markus; Mönig, Harry (ACS Nano)
Keywords: General Physics and Astronomy; General Engineering; General Materials Science

On the Role of Hydrogen Bond Strength and Charge Transfer of a Diels-Alder Reaction On-Water: Semiempirical and Free Energy Calculations. - Henao Aristizabal, Andres; Gohar, Yomna; Whilhelm, René; Kühne, Thomas
Accelerated chemistry at the interface with water has received increasing attention. The mechanisms behind the enhanced reactivity On-Water are not yet clear. In this work we use a Langevin scheme in the spirit of second generation Car-Parrinello to accelerate the second-order density functional Tight-Binding (DFTB2) method in order to investigate the free energy of two Diels-Alder reaction On-Water: the cycloaddition between cyclopentadiene and ethyl cinnamate or thionocinnamate. The only difference between the reactants is the substitution of a carbonyl oxygen for a thiocarbonyl sulfur, making possible the distinction between them as strong and weak hydrogen-bond acceptors. We find a different mechanism for the reaction during the transition states and uncover the role of hydrogen bonds along with the reaction path. Our results suggest that acceleration of Diels-Alder reactions do not arise from an increased number of hydrogen bonds at the transition state and charge transfer plays a significant role. However, the presence of water and hydrogen-bonds is determinant for the catalysis of these reactions.

CENT2: Improved charge equilibration via neural network technique - Khajehpasha, Ehsan Rahmatizad; Finkler, Jonas A.; Kühne, Thomas; Ghasemi, Alireza (Physical Review B)

Surface Passivation and Detrimental Heat-Induced Diffusion Effects in RbF-Treated Cu(In,Ga)Se2 Solar Cell Absorbers - Elizabeth, Amala; Sahoo, Sudhir K.; Phirke, Himanshu; Kodalle, Tim; Kühne, Thomas; Audinot, Jean-Nicolas; Wirtz, Tom; Redinger, Alex; Kaufmann, Christian A.; Mirhosseini, Hossein; Mönig, Harry (ACS Applied Materials & Interfaces)
Keywords: General Materials Science

Fingerprints Indicating Superior Properties of Internal Interfaces in Cu(In,Ga)Se 2 Thin‐Film Solar Cells - Raghuwanshi, Mohit; Chugh, Manjusha; Sozzi, Giovanna; Kanevce, Ana; Kühne, Thomas; Mirhosseini, Hossein; Wuerz, Roland; Cojocaru‐Mirédin, Oana (Advanced Materials)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Do Lead Halide Hybrid Perovskites Have Hydrogen Bonds? - Ibaceta-Jaña, Josefa; Chugh, Manjusha; Novikov, Alexander S.; Mirhosseini, Hossein; Kühne, Thomas; Szyszka, Bernd; Wagner, Markus R.; Muydinov, Ruslan (The Journal of Physical Chemistry C)
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

Ni-based electrocatalysts for unconventional CO2 reduction reaction to formic acid - Lepre, Enrico; Heske, Julian Joachim; Nowakowski, Michal; Scoppola, Ernesto; Zizak, Ivo; Heil, Tobias; Kühne, Thomas; Antonietti, Markus; López-Salas, Nieves; Albero, Josep (Nano Energy)
Keywords: Electrical and Electronic Engineering; General Materials Science; Renewable Energy; Sustainability and the Environment

Time resolved THz-Raman spectroscopy reveals that cations and anions distinctly modify intermolecular interactions of water - Balos, Vasileios; Kaliannan, Naveen Kumar; Elgabarty, Hossam; Wolf, Martin; Kühne, Thomas; Sajadi, Mohsen

“Red Carbon”: A Rediscovered Covalent Crystalline Semiconductor - Odziomek, Mateusz; Giusto, Paolo; Kossmann, Janina; Tarakina, Nadezda V.; Heske, Julian Joachim; Rivadeneira, Salvador M.; Keil, Waldemar; Schmidt, Claudia; Mazzanti, Stefano; Savateev, Oleksandr; Perdigón‐Toro, Lorena; Neher, Dieter; et al. (Advanced Materials)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Challenges in the interpretation of gas core levels for the determination of gas-solid interactions within dielectric porous films by ambient pressure XPS - de los Arcos, Teresa; Weinberger, Christian; Zysk, Frederik; Raj Damerla, Varun; Kollmann, Sabrina; Vieth, Pascal; Tiemann, Michael; Kühne, Thomas; Grundmeier, Guido (Applied Surface Science)
Near ambient pressure XPS in nitrogen atmosphere was utilized to investigate gas-solid interactions within porous SiO2 films ranging from 30 to 75 nm thickness. The films were differentiated in terms of porosity and roughness. The XPS N1s core levels of the N2 gas in presence of the SiO2 samples showed variations in width, binding energy and line shape. The width correlated with the surface charge induced in the dielectric films upon X-ray irradiation. The observed different binding energies observed for the N1s peak can only partly be associated with intrinsic work function differences between the samples, opening the possibility that the effect of physisorption at room temperature could be detected by a shift in the measured binding energy. However, the signals also show an increasing asymmetry with rising surface charge. This might be associated with the formation of vertical electrical gradients within the dielectric porous thin films, which complicates the assignment of binding energy positions to specific surface-related effects. With the support of Monte Carlo and first principles density functional theory calculations, the observed shifts were discussed in terms of the possible formation of transitory dipoles upon N2 physisorption within the porous SiO2 films.
Keywords: Surfaces; Coatings and Films; Condensed Matter Physics; Surfaces and Interfaces; General Physics and Astronomy; General Chemistry

The Structure of Water in Silica Mesopores – Influence of the Pore Wall Polarity - Weinberger, Christian; Zysk, Frederik; Hartmann, Marc; Kaliannan, Naveen; Keil, Waldemar; Kühne, Thomas; Tiemann, Michael (Advanced Materials Interfaces)
In the spatial confinement of cylindrical mesopores with diameters of a few nanometers, water molecules experience restrictions in hydrogen bonding. This leads to a different behavior regarding the molecular orientational freedom (‘structure of water') compared to the bulk liquid state. In addition to the pore size, the behavior is also strongly affected by the strength of the pore wall-to-water interactions, that is, the pore wall polarity. In this work, this is studied both experimentally and theoretically. The surface polarity of mesoporous silica (SiO2) is modified by functionalization with trimethylsilyl moieties, resulting in a change from a hydrophilic (pristine) to a hydrophobic pore wall. The mesopore surface is characterized by N2 and H2O sorption experiments. Those results are combined with IR spectroscopy to investigate pore wall-to-water interactions leading to different structures of water in the mesopore. Furthermore, the water's structure is studied theoretically to gain deeper insight into the interfacial interactions. For this purpose, the structure of water is analyzed by pairing densities, coordination, and angular distributions with a novel adaptation of surface-specific sum-frequency generation calculation for pore environments.
Keywords: Mechanical Engineering; Mechanics of Materials

Raman Optical Activity of N-Acetyl-L-Cysteine in Water and in Methanol: The “Clusters-in-a-Liquid” Model and ab initio Molecular Dynamics Simulations - Yang, Y.; Cheramy, J.; Brehm, Martin; Xu, Y. (ChemPhysChem)

Transferable Deep Learning Potential Reveals Intermediate-Range Ordering Effects in LiF–NaF–ZrF4 Molten Salt - Chahal, R.; Roy, S.; Brehm, Martin; Banerjee, S.; Bryantsev, V.; Lam, S. (JACS Au)

Conformer Weighting and Differently Sized Cluster Weighting for Nicotine and its Phosphorus Derivatives - Taherivardanjani, S.; Blasius, J.; Brehm, Martin; Dötzer, R.; Kirchner, B. (J. Phys. Chem. A)

Cluster Analysis in Liquids: A Novel Tool in TRAVIS - Frömbgen, T.; Blasius, J.; Alizadeh, V.; Chaumont, A.; Brehm, Martin; Kirchner, B. (J. Chem. Inf. Model.)

CP2K on the road to exascale - Kühne, Thomas; Plessl, Christian; Schade, Robert; Schütt, Ole (arXiv:2205.14741)
The CP2K program package, which can be considered as the swiss army knife of atomistic simulations, is presented with a special emphasis on ab-initio molecular dynamics using the second-generation Car-Parrinello method. After outlining current and near-term development efforts with regards to massively parallel low-scaling post-Hartree-Fock and eigenvalue solvers, novel approaches on how we plan to take full advantage of future low-precision hardware architectures are introduced. Our focus here is on combining our submatrix method with the approximate computing paradigm to address the immanent exascale era.

Towards electronic structure-based ab-initio molecular dynamics simulations with hundreds of millions of atoms - Schade, Robert; Kenter, Tobias; Elgabarty, Hossam; Lass, Michael; Schütt, Ole; Lazzaro, Alfio; Pabst, Hans; Mohr, Stephan; Hutter, Jürg; Kühne, Thomas; Plessl, Christian (Parallel Computing)
Keywords: Artificial Intelligence; Computer Graphics and Computer-Aided Design; Computer Networks and Communications; Hardware and Architecture; Theoretical Computer Science; Software

Guanine condensates as covalent materials and the concept of cryptopores - Kossmann, Janina; Piankova, Diana; V. Tarakina, Nadezda; Heske, Julian Joachim; Kühne, Thomas; Schmidt, Johannes; Antonietti, Markus; López-Salas, Nieves (Carbon)
Simple thermal treatment of guanine at temperatures ranging from 600 to 700 °C leads to C1N1 condensates with unprecedented CO2/N2 selectivity when compared to other carbonaceous solid sorbents. Increasing the surface area of the CN condensates in the presence of ZnCl2 salt melts enhances the amount of CO2 adsorbed while preserving the high selectivity values and C1N1 structure. Results indicate that these new materials show a sorption mechanism a step closer to that of natural CO2 caption proteins and based on metal free structural cryptopores.
Keywords: CN; Cryptopores; Carbon dioxide capture

Interfacial Covalent Bonds Regulated Electron-Deficient 2D Black Phosphorus for Electrocatalytic Oxygen Reactions - Wang, Xia; Kormath Madam Raghupathy, Ramya; Querebillo, Christine Joy; Liao, Zhongquan; Li, Dongqi; Lin, Kui; Hantusch, Martin; Sofer, Zdeněk; Li, Baohua; Zschech, Ehrenfried; Weidinger, Inez M.; Kühne, Thomas; et al. (Advanced Materials)
Abstract Developing resource-abundant and sustainable metal-free bifunctional oxygen electrocatalysts is essential for the practical application of zinc–air batteries (ZABs). 2D black phosphorus (BP) with fully exposed atoms and active lone pair electrons can be promising for oxygen electrocatalysts, which, however, suffers from low catalytic activity and poor electrochemical stability. Herein, guided by density functional theory (DFT) calculations, an efficient metal-free electrocatalyst is demonstrated via covalently bonding BP nanosheets with graphitic carbon nitride (denoted BP-CN-c). The polarized PN covalent bonds in BP-CN-c can efficiently regulate the electron transfer from BP to graphitic carbon nitride and significantly promote the OOH* adsorption on phosphorus atoms. Impressively, the oxygen evolution reaction performance of BP-CN-c (overpotential of 350 mV at 10 mA cm−2, 90% retention after 10 h operation) represents the state-of-the-art among the reported BP-based metal-free catalysts. Additionally, BP-CN-c exhibits a small half-wave overpotential of 390 mV for oxygen reduction reaction, representing the first bifunctional BP-based metal-free oxygen catalyst. Moreover, ZABs are assembled incorporating BP-CN-c cathodes, delivering a substantially higher peak power density (168.3 mW cm−2) than the Pt/C+RuO2-based ZABs (101.3 mW cm−2). The acquired insights into interfacial covalent bonds pave the way for the rational design of new and affordable metal-free catalysts.
Keywords: 2D materials; bifunctional oxygen electrocatalysts; black phosphorus; oxygen evolution reaction; zinc–air batteries

Thermodynamically stable polymorphs of nitrogen-rich carbon nitrides: a C3N5 study - Ghasemi, Alireza; Mirhosseini, Hossein; Kühne, Thomas (Phys. Chem. Chem. Phys.)
We have carried out an extensive search for stable polymorphs of carbon nitride with C3N5 stoichiometry using the minima hopping method. Contrary to the widely held opinion that stacked{,} planar{,} graphite-like structures are energetically the most stable carbon nitride polymorphs for various nitrogen contents{,} we find that this does not apply for nitrogen-rich materials owing to the high abundance of N–N bonds. In fact{,} our results disclose novel morphologies with moieties not previously considered for C3N5. We demonstrate that nitrogen-rich compounds crystallize in a large variety of different structures due to particular characteristics of their energy landscapes. The newly found low-energy structures of C3N5 have band gaps within good agreement with the values measured in experimental studies.

Mixed‐Valence Compounds as Polarizing Agents for Overhauser Dynamic Nuclear Polarization in Solids - Gurinov, Andrei; Sieland, Benedikt; Kuzhelev, Andrey; Elgabarty, Hossam; Kühne, Thomas; Prisner, Thomas; Paradies, Jan; Baldus, Marc; Ivanov, Konstantin L.; Pylaeva, Svetlana (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

Artificial neural networks for the kinetic energy functional of non-interacting fermions - Ghasemi, S. Alireza; Kühne, Thomas D. (The Journal of Chemical Physics)

On topological materials as photocatalysts for water splitting by visible light - Ranjbar, Ahmad; Mirhosseini, Hossein; Kühne, Thomas D (Journal of Physics: Materials)
Abstract We performed a virtual materials screening to identify promising topological materials for photocatalytic water splitting under visible light irradiation. Topological compounds were screened based on band gap, band edge energy, and thermodynamics stability criteria. In addition, topological types for our final candidates were computed based on electronic structures calculated usingthe hybrid density functional theory including exact Hartree–Fock exchange. Our final list contains materials which have band gaps between 1.0 and 2.7 eV in addition to band edge energies suitable for water oxidation and reduction. However, the topological types of these compounds calculated with the hybrid functional differ from those reported previously. To that end, we discuss the importance of computational methods for the calculation of atomic and electronic structures in materials screening processes.
Keywords: Condensed Matter Physics; General Materials Science; Atomic and Molecular Physics; and Optics

When water becomes an integral part of carbon – combining theory and experiment to understand the zeolite-like water adsorption properties of porous C2N materials - Heske, Julian Joachim; Walczak, Ralf; Epping, Jan D.; Youk, Sol; Sahoo, Sudhir K.; Antonietti, Markus; Kühne, Thomas; Oschatz, Martin (Journal of Materials Chemistry A)
The origin of strong interactions between water molecules and porous C 2 N surfaces is investigated by using a combination of model materials, volumetric physisorption measurements, solid-state NMR spectroscopy, and DFT calculations.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Hydrogen bond dynamics of interfacial water molecules revealed from two-dimensional vibrational sum-frequency generation spectroscopy - Ojha, Deepak; Kühne, Thomas (Scientific Reports)
Abstract Vibrational sum-frequency generation (vSFG) spectroscopy allows the study of the structure and dynamics of interfacial systems. In the present work, we provide a simple recipe, based on a narrowband IR pump and broadband vSFG probe technique, to computationally obtain the two-dimensional vSFG spectrum of water molecules at the air–water interface. Using this technique, to study the time-dependent spectral evolution of hydrogen-bonded and free water molecules, we demonstrate that at the interface, the vibrational spectral dynamics of the free OH bond is faster than that of the bonded OH mode.
Keywords: Multidisciplinary

Organic Mixed-Valence Compounds and the Overhauser Effect in Insulating Solids - Pylaeva, Svetlana; Marx, Patrick; Singh, Gurjot; Kühne, Thomas; Roemelt, Michael; Elgabarty, Hossam (The Journal of Physical Chemistry A)
Keywords: Physical and Theoretical Chemistry

Artificial Neural Networks as Trial Wave Functions for Quantum Monte Carlo - Kessler, Jan; Calcavecchia, Francesco; Kühne, Thomas (Advanced Theory and Simulations)
Keywords: Multidisciplinary; Modeling and Simulation; Numerical Analysis; Statistics and Probability

Artificial neural networks for the kinetic energy functional of non-interacting fermions - Ghasemi, Alireza; Kühne, Thomas (The Journal of Chemical Physics)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

A combinatorial study of electrochemical anion intercalation into graphite - Chugh, Manjusha; Jain, Mitisha; Wang, Gang; Nia, Ali Shaygan; Mirhosseini, Hossein; Kühne, Thomas (Materials Research Express)
Abstract Dual-ion batteries are considered to be an emerging viable energy storage technology owing to their safety, high power capability, low cost, and scalability. Intercalation of anions into a graphite positive electrode provides high operating voltage and improved energy density to such dual-ion batteries. In this work, we have performed a combinatorial study of graphite intercalation compounds considering four anions, namely hexafluorophosphate (PF <?CDATA ${}_{6}^{-}$?> 6 − ), perchlorate (ClO <?CDATA ${}_{4}^{-}$?> 4 − ), bis(fluorosulfonyl)imide (FSI − ), and bis(trifluoromethanesulfonyl)imide (TFSI − ), via first-principles calculations. The structural properties and energetics of the intercalation compounds are compared based on different sizes, geometries, and the physical and chemical properties of the intercalated anions. The staging mechanism of anion intercalation into graphite and the specific capacities, and voltage profiles of the intercalated compounds are investigated. A comparison regarding battery electrochemistry is also done with available experimental observations. Our calculated intercalation energies and voltage profiles show that the initial anion intercalation into graphite is less favorable than subsequent ones for all the anions considered in this study. Although the effect of the size of anions in a graphite cathode on various properties of the intercalated compounds is not as significant as the size of cations in a graphite anode, some distinction between the studied anions can still be made. Among the studied anions, the intercalation compounds based on PF <?CDATA ${}_{6}^{-}$?> 6 − are the most stable ones. These PF <?CDATA ${}_{6}^{-}$?> 6 − anions cause relatively small structural deformations of the graphite and have the highest oxidative ability, highest onset voltage, and highest diffusion barrier along the graphene sheets. The overall small diffusion barriers of the anions within graphite explain the high rate capability of dual-ion batteries.
Keywords: Metals and Alloys; Polymers and Plastics; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Full Assignment of Ab-Initio Raman Spectra at Finite Temperatures Using Wannier Polarizabilities: Application to Cyclohexane Molecule in Gas Phase - Partovi-Azar, Pouya; Kühne, Thomas (Micromachines)
We demonstrate how to fully ascribe Raman peaks simulated using ab initio molecular dynamics to specific vibrations in the structure at finite temperatures by means of Wannier functions. Here, we adopt our newly introduced method for the simulation of the Raman spectra in which the total polarizability of the system is expressed as a sum over Wannier polarizabilities. The assignment is then based on the calculation of partial Raman activities arising from self- and/or cross-correlations between different types of Wannier functions in the system. Different types of Wannier functions can be distinguished based on their spatial spread. To demonstrate the predictive power of this approach, we applied it to the case of a cyclohexane molecule in the gas phase and were able to fully assign the simulated Raman peaks.
Keywords: Electrical and Electronic Engineering; Mechanical Engineering; Control and Systems Engineering

Photocatalytic Water Splitting Reaction Catalyzed by Ion-Exchanged Salts of Potassium Poly(heptazine imide) 2D Materials - Sahoo, Sudhir K.; Teixeira, Ivo F.; Naik, Aakash; Heske, Julian Joachim; Cruz, Daniel; Antonietti, Markus; Savateev, Aleksandr; Kühne, Thomas (The Journal of Physical Chemistry C)
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

An automated approach for developing neural network interatomic potentials with FLAME - Mirhosseini, Hossein; Tahmasbi, Hossein; Kuchana, Sai Ram; Ghasemi, Alireza; Kühne, Thomas (Computational Materials Science)
Keywords: Computational Mathematics; General Physics and Astronomy; Mechanics of Materials; General Materials Science; General Chemistry; General Computer Science

Ultrafast solvent-to-solvent and solvent-to-solute energy transfer driven by single-cycle THz electric fields - Balos, Vasileios; Elgabarty, Hossam; Wolf, Martin; Kühne, Thomas; Netz, Roland; Bonthuis, Douwe Jan; Kaliannan, Naveen; Loche, Philip; Kampfrath, Tobias; Sajadi, Mohsen (Terahertz Emitters, Receivers, and Applications XII)

A theoretical investigation of topological phase modulation in carbide MXenes: Role of image potential states - Wang, Mengying; Ranjbar, Ahmad; Kühne, Thomas; Belosludov, Rodion V.; Kawazoe, Yoshiyuki; Liang, Yunye (Carbon)
Keywords: General Chemistry; General Materials Science

On topological materials as photocatalysts for water splitting by visible light - Ranjbar, Ahmad; Mirhosseini, Hossein; Kühne, Thomas (Journal of Physics: Materials)
Abstract We performed a virtual materials screening to identify promising topological materials for photocatalytic water splitting under visible light irradiation. Topological compounds were screened based on band gap, band edge energy, and thermodynamics stability criteria. In addition, topological types for our final candidates were computed based on electronic structures calculated usingthe hybrid density functional theory including exact Hartree–Fock exchange. Our final list contains materials which have band gaps between 1.0 and 2.7 eV in addition to band edge energies suitable for water oxidation and reduction. However, the topological types of these compounds calculated with the hybrid functional differ from those reported previously. To that end, we discuss the importance of computational methods for the calculation of atomic and electronic structures in materials screening processes.
Keywords: Condensed Matter Physics; General Materials Science; Atomic and Molecular Physics; and Optics

Sustainable oxidation catalysis supported by light: Fe-poly (heptazine imide) as a heterogeneous single-atom photocatalyst - da Silva, Marcos A.R.; Silva, Ingrid F.; Xue, Qi; Lo, Benedict T.W.; Tarakina, Nadezda V.; Nunes, Barbara N.; Adler, Peter; Sahoo, Sudhir K.; Bahnemann, Detlef W.; López-Salas, Nieves; Savateev, Aleksandr; Ribeiro, Caue; et al. (Applied Catalysis B: Environmental)
Keywords: Process Chemistry and Technology; General Environmental Science; Catalysis

Influence of different ester side groups in polymers on the vapor phase infiltration with trimethyl aluminum - Mai, Lukas; Maniar, Dina; Zysk, Frederik; Schöbel, Judith; Kühne, Thomas; Loos, Katja; Devi, Anjana (Dalton Transactions)
The influence of different polymer side chains on the vapor phase infiltration with TMA is investigated and supported by DFT-calculations.
Keywords: Inorganic Chemistry

A Force Field for Bio-Polymers in Ionic Liquids (BILFF) – Part 1: [EMIm][OAc] / Water Mixtures - Roos, E.; Brehm, Martin (Phys. Chem. Chem. Phys.)

Optimized Atomic Partial Charges and Radii Defined by Radical Voronoi Tessellation of Bulk Phase Simulations - Brehm, Martin; Thomas, M. (Molecules)

Unraveling Local Structure of Molten Salts via X-Ray Scattering, Raman Spectroscopy, and ab initio Molecular Dynamics - Roy, S.; Brehm, Martin; Sharma, S.; Wu, F.; Maltsev, D.; Halstenberg, P.; Gallington, L.; Mahurin, S.; Dai, S.; Ivanov, A.; Margulis, C.; Bryantsev, V. (J. Phys. Chem. B)

Liquid Structure and Dynamics in the Choline Acetate:Urea 1:2 Deep Eutectic Solvent - Triolo, A.; Pietro, M. E. Di; Mele, A.; Celso, F. Lo; Brehm, Martin; Lisio, V. Di; Martinelli, A.; Chater, P.; Russina, O. (J. Chem. Phys.)

Switching Between Proton Vacancy and Excess Proton Transfer Pathways in the Reaction Between 7-Hydroxyquinoline and Formate - Codescu, M.-A.; Weiß, M.; Brehm, Martin; Kornilov, O.; Sebastiani, D.; Nibbering, E. T. J. (J. Phys. Chem. A)

Efficient EOM-CC-Based Protocol for the Calculation of Electron Affinity of Solvated Nucleobases: Uracil as a Case Study - Mukherjee, M.; Tripathi, D.; Brehm, Martin; Riplinger, C.; Dutta, A. K. (J. Chem. Theory Comput.)

Liquid Structure of a Choline Chloride-Water Natural Deep Eutectic Solvent: A Molecular Dynamics Characterization - Triolo, A.; Celso, F. Lo; Brehm, Martin; Lisio, V. Di; Russina, O. (J. Mol. Liq.)

Evaluating the Design Space for Offloading 3D FFT Calculations to an FPGA for High-Performance Computing - Ramaswami, Arjun; Kenter, Tobias; Kühne, Thomas; Plessl, Christian (Applied Reconfigurable Computing. Architectures, Tools, and Applications)

“On-The-Fly” Calculation of the Vibrational Sum-Frequency Generation Spectrum at the Air-Water Interface - Ojha, Deepak; Kühne, Thomas D. (Molecules)
In the present work, we provide an electronic structure based method for the “on-the-fly” determination of vibrational sum frequency generation (v-SFG) spectra. The predictive power of this scheme is demonstrated at the air-water interface. While the instantaneous fluctuations in dipole moment are obtained using the maximally localized Wannier functions, the fluctuations in polarizability are approximated to be proportional to the second moment of Wannier functions. The spectrum henceforth obtained captures the signatures of hydrogen bond stretching, bending, as well as low-frequency librational modes.

Disordered crystals from first principles II: Transport coefficients - Kühne, Thomas; Heske, Julian Joachim; Prodan, Emil (Annals of Physics)
This is the second part of a project on the foundations of first-principle calculations of the electron transport in crystals at finite temperatures, aiming at a predictive first-principles platform that combines ab-initio molecular dynamics (AIMD) and a finite-temperature Kubo-formula with dissipation for thermally disordered crystalline phases. The latter are encoded in an ergodic dynamical system (Ω,G,dP), where Ω is the configuration space of the atomic degrees of freedom, G is the space group acting on Ω and dP is the ergodic Gibbs measure relative to the G-action. We first demonstrate how to pass from the continuum Kohn–Sham theory to a discrete atomic-orbitals based formalism without breaking the covariance of the physical observables w.r.t. (Ω,G,dP). Then we show how to implement the Kubo-formula, investigate its self-averaging property and derive an optimal finite-volume approximation for it. We also describe a numerical innovation that made possible AIMD simulations with longer orbits and elaborate on the details of our simulations. Lastly, we present numerical results on the transport coefficients of crystal silicon at different temperatures.

Insight from energy decomposition analysis on a hydrogen-bond-mediated mechanism for on-water catalysis - Salem, M. Alaraby; Kühne, Thomas D. (Molecular Physics)

Correlating facet orientation, defect-level density and dipole layer formation at the surface of polycrystalline CuInSe2 thin films - Elizabeth, Amala; Conradi, Hauke; K. Sahoo, Sudhir; Kodalle, Tim; A. Kaufmann, Christian; Kühne, Thomas; Mirhosseini, Hossein; Abou-Ras, Daniel; Mönig, Harry (Acta Materialia)
Individual grains of chalcopyrite solar cell absorbers can facet in different crystallographic directions at their surfaces. To gain a deeper understanding of the junction formation in these devices, we correlate variations in the surface facet orientation with the defect electronic properties. We use a combined analytical approach based on scanning tunneling spectroscopy (STS), scanning electron microscopy, and electron back scatter diffraction (EBSD), where we perform these experiments on identical surface areas as small as 2 × 2 µm2 with a lateral resolution well below 50 nm. The topography of the absorber surfaces indicates two main morphological features: micro-faceted, long basalt-like columns and their short nano-faceted terminations. Our STS results reveal that the long columns exhibit spectral signatures typical for the presence of pronounced oxidation-induced surface dipoles in conjunction with an increased density of electronic defect levels. In contrast, the nano-faceted terminations of the basalt-like columns are largely passivated in terms of electronic defect levels within the band gap region. Corresponding crystallographic data based on EBSD experiments show that the surface of the basalt-like columns can be assigned to intrinsically polar facet orientations, while the passivated terminations are assigned to non-polar planes. Ab-initio calculations suggest that the polar surfaces are more prone to oxidation and resulting O-induced defects, in comparison to non-polar planes. Our results emphasize the correlation between morphology, surface facet orientations and surface electronic properties. Furthermore, this work aids in gaining a fundamental understanding of oxidation induced lateral inhomogeneities in view of the p-n junction formation in chalcopyrite thin-film solar cells.
Keywords: Chalcopyrite absorber; Scanning tunneling spectroscopy; Electron backscatter diffraction; Density functional theory; Surface dipole

Electrochemical N2 Reduction to Ammonia Using Single Au/Fe Atoms Supported on Nitrogen-Doped Porous Carbon - Sahoo, Sudhir K.; Heske, Julian Joachim; Antonietti, Markus; Qin, Qing; Oschatz, Martin; Kühne, Thomas (ACS Applied Energy Materials)
The electrochemical nitrogen reduction reaction (NRR) to ammonia (NH3) is a promising alternative route for an NH3 synthesis at ambient conditions to the conventional high temperature and pressure Haber--Bosch process without the need for hydrogen gas. Single metal ions or atoms are attractive candidates for the catalytic activation of non-reactive nitrogen (N2), and for future targeted improvement of NRR catalysts, it is of utmost importance to get detailed insights into structure-performance relationships and mechanisms of N2 activation in such structures. Here, we report density functional theory studies on the NRR catalyzed by single Au and Fe atoms supported in graphitic C2N materials. Our results show that the metal atoms present in the structure of C2N are the reactive sites, which catalyze the aforesaid reaction by strong adsorption and activation of N2. We further demonstrate that a lower onset electrode potential is required for Fe--C2N than for Au--C2N. Thus, Fe--C2N is theoretically predicted to be a potentially better NRR catalyst at ambient conditions than Au--C2N owing to the larger adsorption energy of N2 molecules. Furthermore, we have experimentally shown that single sites of Au and Fe supported on nitrogen-doped porous carbon are indeed active NRR catalysts. However, in contrast to our theoretical results, the Au-based catalyst performed slightly better with a Faradaic efficiency (FE) of 10.1{%} than the Fe-based catalyst with an FE of 8.4{%} at −0.2 V vs. RHE. The DFT calculations suggest that this difference is due to the competitive hydrogen evolution reaction and higher desorption energy of ammonia.

Modulation of nearly free electron states in hydroxyl-functionalized MXenes: a first-principles study - Zhou, Jiaqi; Khazaei, Mohammad; Ranjbar, Ahmad; Wang, Vei; Kühne, Thomas D.; Ohno, Kaoru; Kawazoe, Yoshiyuki; Liang, Yunye (J. Mater. Chem. C)

On the Possibility of Helium Adsorption in Nitrogen Doped Graphitic Materials - Kumar Sahoo, Sudhir; Heske, Julian Joachim; Azadi, Sam; Zhang, Zhenzhe; V Tarakina, Nadezda; Oschatz, Martin; Z. Khaliullin, Rustam; Antonietti, Markus; Kühne, Thomas (Scientific Reports)

Energy transfer within the hydrogen bonding network of water following resonant terahertz excitation - Elgabarty, Hossam; Kampfrath, Tobias; Bonthuis, Douwe Jan; Balos, Vasileios; Kaliannan, Naveen Kumar; Loche, Philip; Netz, Roland R.; Wolf, Martin; K{\, Thomas D.; Sajadi, Mohsen (Science Advances)

CP2K: An electronic structure and molecular dynamics software package - Quickstep: Efficient and accurate electronic structure calculations - Kühne, Thomas D.; Iannuzzi, Marcella; Del Ben, Mauro; Rybkin, Vladimir V.; Seewald, Patrick; Stein, Frederick; Laino, Teodoro; Khaliullin, Rustam Z.; Schütt, Ole; Schiffmann, Florian; al., et (The Journal of Chemical Physics)

Oxidation/reduction cycles and their reversible effect on the dipole formation at CuInSe2 surfaces - Elizabeth, Amala; Sahoo, Sudhir K.; Lockhorn, David; Timmer, Alexander; Aghdassi, Nabi; Zacharias, Helmut; Kühne, Thomas; Siebentritt, Susanne; Mirhosseini, Hossein; Mönig, Harry (Phys. Rev. Materials)
The defect-electronic properties of {112} microfaceted surfaces of epitaxially grown CuInSe2 thin films are investigated by scanning tunneling spectroscopy and photoelectron spectroscopy techniques after various surface treatments. The intrinsic CuInSe2 surface is found to be largely passivated in terms of electronic defect levels in the band-gap region. However, surface oxidation leads to an overall high density of defect levels in conjunction with a considerable net surface dipole, which persists even after oxide removal. Yet, a subsequent annealing under vacuum restores the initial condition. Such oxidation/reduction cycles are reversible for many times providing robust control of the surface and interface properties in these materials. Based on ab initio simulations, a mechanism where oxygen dissociatively adsorbs and subsequently diffuses to a subsurface site is proposed as the initial step of the observed dipole formation. Our results emphasize the relevance of oxidation-induced dipole effects at the thin film surface and provide a comprehensive understanding toward passivation strategies of these surfaces.

In silico investigation of Cu(In,Ga)Se2-based solar cells - Mirhosseini, S. Hossein; Kormath Madam Raghupathy, Ramya; Sahoo, Sudhir K.; Wiebeler, Hendrik; Chugh, Manjusha; Kühne, Thomas (Phys. Chem. Chem. Phys.)
Photovoltaics is one of the most promising and fastest-growing renewable energy technologies. Although the price-performance ratio of solar cells has improved significantly over recent years{,} further systematic investigations are needed to achieve higher performance and lower cost for future solar cells. In conjunction with experiments{,} computer simulations are powerful tools to investigate the thermodynamics and kinetics of solar cells. Over the last few years{,} we have developed and employed advanced computational techniques to gain a better understanding of solar cells based on copper indium gallium selenide (Cu(In{,}Ga)Se2). Furthermore{,} we have utilized state-of-the-art data-driven science and machine learning for the development of photovoltaic materials. In this Perspective{,} we review our results along with a survey of the field.

A High-Rate Two-Dimensional Polyarylimide Covalent Organic Framework Anode for Aqueous Zn-Ion Energy Storage Devices - Yu, Minghao; Chandrasekhar, Naisa; Kormath Madam Raghupathy, Ramya; Ly, Khoa Hoang; Zhang, Haozhe; Dmitrieva, Evgenia; Liang, Chaolun; Lu, Xihong; Kühne, Thomas; Mirhosseini, S. Hossein; Weidinger, Inez M.; Feng, Xinliang (Journal of the American Chemical Society)
Rechargeable aqueous Zn-ion energy storage devices are promising candidates for next-generation energy storage technologies. However, the lack of highly reversible Zn2+-storage anode materials with low potential windows remains a primary concern. Here, we report a two-dimensional polyarylimide covalent organic framework (PI-COF) anode with high-kinetics Zn2+-storage capability. The well-organized pore channels of PI-COF allow the high accessibility of the build-in redox-active carbonyl groups and efficient ion diffusion with a low energy barrier. The constructed PI-COF anode exhibits a specific capacity (332 C g–1 or 92 mAh g–1 at 0.7 A g–1), a high rate capability (79.8% at 7 A g–1), and a long cycle life (85% over 4000 cycles). In situ Raman investigation and first-principle calculations clarify the two-step Zn2+-storage mechanism, in which imide carbonyl groups reversibly form negatively charged enolates. Dendrite-free full Zn-ion devices are fabricated by coupling PI-COF anodes with MnO2 cathodes, delivering excellent energy densities (23.9 ∼ 66.5 Wh kg–1) and supercapacitor-level power densities (133 ∼ 4782 W kg–1). This study demonstrates the feasibility of covalent organic framework as Zn2+-storage anodes and shows a promising prospect for constructing reliable aqueous energy storage devices.

Vibrational dynamics in lead halide hybrid perovskites investigated by Raman spectroscopy - Ibaceta-Jaña, Josefa; Muydinov, Ruslan; Rosado, Pamela; Mirhosseini, Hossein; Chugh, Manjusha; Nazarenko, Olga; Dirin, Dmitry N.; Heinrich, Dirk; Wagner, Markus R.; Kühne, Thomas; Szyszka, Bernd; Kovalenko, Maksym V.; et al. (Phys. Chem. Chem. Phys.)
Lead halide perovskite semiconductors providing record efficiencies of solar cells have usually mixed compositions doped in A- and X-sites to enhance the phase stability. The cubic form of formamidinium (FA) lead iodide reveals excellent opto-electronic properties but transforms at room temperature (RT) into a hexagonal structure which does not effectively absorb visible light. This metastable form and the mechanism of its stabilization by Cs+ and Br− incorporation are poorly characterized and insufficiently understood. We report here the vibrational properties of cubic FAPbI3 investigated by DFT calculations on phonon frequencies and intensities, and micro-Raman spectroscopy. The effects of Cs+ and Br− partial substitution are discussed. We support our results with the study of FAPbBr3 which expands the identification of vibrational modes to the previously unpublished low frequency region (<500 cm−1). Our results show that the incorporation of Cs+ and Br− leads to the coupling of the displacement of the A-site components and weakens the bonds between FA+ and the PbX6 octahedra. We suggest that the enhancement of α-FAPbI3 stability can be a product of the release of tensile stresses in the Pb–X bond, which is reflected in a red-shift of the low frequency region of the Raman spectrum (<200 cm−1).

Revealing the origin of the beneficial effect of cesium in highly efficient Cu(In,Ga)Se2 solar cells - Schöppe, Philipp; Schönherr, Sven; Chugh, Manjusha; Mirhosseini, Hossein; Jackson, Philip; Wuerz, Roland; Ritzer, Maurizio; Johannes, Andreas; Martínez-Criado, Gema; Wisniewski, Wolfgang; Schwarz, Torsten; T. Plass, Christian; et al. (Nano Energy)
The record conversion efficiency of thin-film solar cells based on Cu(In,Ga)Se2 (CIGS) absorbers has exceeded 23%. Such a high performance is currently only attainable by the incorporation of heavy alkali metals like Cs into the absorber through an alkali fluoride post-deposition treatment (PDT). As the effect of the incorporated heavy alkali metals is under discussion, we investigated the local composition and microstructure of high efficiency CIGS solar cells via various high-resolution techniques in a combinatory approach. An accumulation of Cs is clearly detected at the p-n junction along with variations in the local CIGS composition, showing the formation of a beneficial secondary phase with a laterally inhomogeneous distribution. Additionally, Cs accumulations were detected at grain boundaries with a random misorientation of the adjacent grains where a reduced Cu concentration and increased In and Se concentrations are detected. No accumulation was found at Σ3 twin boundaries as well as the grain interior. These experimental findings are in excellent agreement with complementary ab-initio calculations, demonstrating that the grain boundaries are passivated by the presence of Cs. Further, it is unlikely that Cs with its large ionic radius is incorporated into the CIGS grains where it would cause detrimental defects.

Effects of KF and RbF treatments on Cu(In,Ga)Se2-based solar cells: A combined photoelectron spectroscopy and DFT study - Majumdar, I.; Sahoo, S.K.; Parvan, V.; Mirhosseini, Hossein; Chacko, B.; Wang, Y.; Greiner, D.; Kühne, Thomas; Schlatmann, R.; Lauermann, I. (Applied Surface Science)
Keywords: Surfaces; Coatings and Films; Condensed Matter Physics; Surfaces and Interfaces; General Physics and Astronomy; General Chemistry

Guanine condensates as covalent materials and the concept of cryptopores - Kossmann, Janina; Piankova, Diana; Tarakina, Nadezda V.; Heske, Julian Joachim; Kühne, Thomas; Schmidt, Johannes; Antonietti, Markus; López-Salas, Nieves (Carbon)
Keywords: General Chemistry; General Materials Science

Exploring Non-Equilibrium Molecular Dynamics of Mobile Protons in the Solid Acid CsH2PO4 on the Micrometer and Microsecond Scale - Dreßler, C.; Kabbe, G.; Brehm, Martin; Sebastiani, D. (J. Chem. Phys.)

Dissolving Cellulose in 1,2,3-Triazolium- and Imidazolium-Based Ionic Liquids with Aromatic Anions - Brehm, Martin; Radicke, J.; Pulst, M.; Shaabani, F.; Sebastiani, D.; Kressler, J. (Molecules)

Characterization of Aqueous Lower Polarity Solvation Shells Around Amphiphilic TEMPO Radicals in Water - Hunold, J.; Eisermann, J.; Brehm, Martin; Hinderberger, D. (J. Phys. Chem. B)

From Flat to Tilted: Gradual Interfaces in Organic Thin Film Growth - Scarbath-Evers, L.; Hammer, R.; Golze, D.; Brehm, Martin; Sebastiani, D.; Widdra, W. (Nanoscale)

Dynamical Matrix Propagator Scheme for Large-Scale Proton Dynamics Simulations - Dreßler, C.; Kabbe, G.; Brehm, Martin; Sebastiani, D. (J. Chem. Phys.)

Exploring Free Energy Profiles of Enantioselective Organocatalytic Aldol Reactions under Full Solvent Influence - Weiß, M.; Brehm, Martin (Molecules)

TRAVIS – A Free Analyzer for Trajectories from Molecular Simulation - Brehm, Martin; Thomas, M.; Gehrke, S.; Kirchner, B. (J. Chem. Phys.)

CP2K: An electronic structure and molecular dynamics software package - Quickstep: Efficient and accurate electronic structure calculations - Kühne, Thomas; Iannuzzi, Marcella; Ben, Mauro Del; Rybkin, Vladimir V.; Seewald, Patrick; Stein, Frederick; Laino, Teodoro; Khaliullin, Rustam Z.; Schütt, Ole; Schiffmann, Florian; Golze, Dorothea; Wilhelm, Jan; et al. (The Journal of Chemical Physics)
CP2K is an open source electronic structure and molecular dynamics software package to perform atomistic simulations of solid-state, liquid, molecular, and biological systems. It is especially aimed at massively parallel and linear-scaling electronic structure methods and state-of-theart ab initio molecular dynamics simulations. Excellent performance for electronic structure calculations is achieved using novel algorithms implemented for modern high-performance computing systems. This review revisits the main capabilities of CP2K to perform efficient and accurate electronic structure simulations. The emphasis is put on density functional theory and multiple post–Hartree–Fock methods using the Gaussian and plane wave approach and its augmented all-electron extension.

A Submatrix-Based Method for Approximate Matrix Function Evaluation in the Quantum Chemistry Code CP2K - Lass, Michael; Schade, Robert; Kühne, Thomas; Plessl, Christian (Proc. International Conference for High Performance Computing, Networking, Storage and Analysis (SC))
Electronic structure calculations based on density-functional theory (DFT) represent a significant part of today's HPC workloads and pose high demands on high-performance computing resources. To perform these quantum-mechanical DFT calculations on complex large-scale systems, so-called linear scaling methods instead of conventional cubic scaling methods are required. In this work, we take up the idea of the submatrix method and apply it to the DFT computations in the software package CP2K. For that purpose, we transform the underlying numeric operations on distributed, large, sparse matrices into computations on local, much smaller and nearly dense matrices. This allows us to exploit the full floating-point performance of modern CPUs and to make use of dedicated accelerator hardware, where performance has been limited by memory bandwidth before. We demonstrate both functionality and performance of our implementation and show how it can be accelerated with GPUs and FPGAs.

Accurate Sampling with Noisy Forces from Approximate Computing - Rengaraj, Varadarajan; Lass, Michael; Plessl, Christian; Kühne, Thomas (Computation)
In scientific computing, the acceleration of atomistic computer simulations by means of custom hardware is finding ever-growing application. A major limitation, however, is that the high efficiency in terms of performance and low power consumption entails the massive usage of low precision computing units. Here, based on the approximate computing paradigm, we present an algorithmic method to compensate for numerical inaccuracies due to low accuracy arithmetic operations rigorously, yet still obtaining exact expectation values using a properly modified Langevin-type equation.

Accessing the Accuracy of Density Functional Theory through Structure and Dynamics of the Water–Air Interface - Ohto, Tatsuhiko; Dodia, Mayank; Xu, Jianhang; Imoto, Sho; Tang, Fujie; Zysk, Frederik; Kühne, Thomas D.; Shigeta, Yasuteru; Bonn, Mischa; Wu, Xifan; Nagata, Yuki (The Journal of Physical Chemistry Letters)

Unconventional phase III of high-pressure solid hydrogen - Azadi, Sam; Kühne, Thomas D. (Physical Review B)

Vibrational Properties of RbInSe2: Raman Scattering Spectroscopy and First-Principle Calculations - Guc, Maxim; Kodalle, Tim; Kormath Madam Raghupathy, Ramya; Mirhosseini, Hossein; Kühne, Thomas D.; Becerril-Romero, Ignacio; Pérez-Rodríguez, Alejandro; Kaufmann, Christian A.; Izquierdo-Roca, Victor (The Journal of Physical Chemistry C)

Experimental and Theoretical High Energy Resolution Hard X-ray Absorption and Emission Spectroscopy on Biomimetic Cu2S2 Complexes - Müller, Patrick; Neuba, Adam; Flörke, Ulrich; Henkel, Gerald; Kühne, Thomas D.; Bauer, Matthias (The Journal of Physical Chemistry A)

Experimental and theoretical (high energy resolution) X-ray absorption and emission spectroscopy / vorgelegt von Patrick Müller ; [Promotionskommission: Prof. Dr.-Ing. Hans-Joachim Warnecke, Vorsitz; Prof. Dr. Matthias Bauer, Erstgutachter; Prof. Dr. Thomas D. Kühne, Zweitgutachter; Prof. Dr. Wolf Gero Schmidt] - Müller, Patrick

Properties of Co-Evaporated RbInSe2 Thin Films - Kodalle, Tim; Kormath Madam Raghupathy, Ramya; Bertram, Tobias; Maticiuc, Natalia; Yetkin, Hasan A; Gunder, René; Schlatmann, Rutger; Kühne, Thomas D; Kaufmann, Christian A; Mirhosseini, Hossein (physica status solidi (RRL)--Rapid Research Letters)

Opposing Electronic and Nuclear Quantum Effects on Hydrogen Bonds in H2O and D2O - Clark, Timothy; Heske, Julian Joachim; Kühne, Thomas (ChemPhysChem)
Abstract The effect of extending the O−H bond length(s) in water on the hydrogen-bonding strength has been investigated using static ab initio molecular orbital calculations. The “polar flattening” effect that causes a slight σ-hole to form on hydrogen atoms is strengthened when the bond is stretched, so that the σ-hole becomes more positive and hydrogen bonding stronger. In opposition to this electronic effect, path-integral ab initio molecular-dynamics simulations show that the nuclear quantum effect weakens the hydrogen bond in the water dimer. Thus, static electronic effects strengthen the hydrogen bond in H2O relative to D2O, whereas nuclear quantum effects weaken it. These quantum fluctuations are stronger for the water dimer than in bulk water.
Keywords: ab initio calculations; bond theory; hydrogen bonds; isotope effects; solvent effects

Impact of intermolecular vibrational coupling effects on the sum-frequency generation spectra of the water/air interface - Kaliannan, Naveen Kumar; Henao Aristizabal, Andres; Wiebeler, Hendrik; Zysk, Frederik; Ohto, Tatsuhiko; Nagata, Yuki; D. Kühne, Thomas (Molecular Physics)

Experimental and Theoretical High Energy Resolution Hard X-ray Absorption and Emission Spectroscopy on Biomimetic Cu2S2 Complexes - Müller, Patrick; Neuba, Adam; Flörke, Ulrich; Henkel, Gerald; Kühne, Thomas D.; Bauer, Matthias (The Journal of Physical Chemistry A)

Controlling the strength of interaction between carbon dioxide and nitrogen-rich carbon materials by molecular design - Walczak, Ralf; Savateev, Aleksandr; Heske, Julian Joachim; Tarakina, Nadezda V.; Sahoo, Sudhir; Epping, Jan D.; Kühne, Thomas; Kurpil, Bogdan; Antonietti, Markus; Oschatz, Martin (Sustainable Energy Fuels)
Thermal treatment of hexaazatriphenylene-hexacarbonitrile (HAT-CN) in the temperature range from 500 °C to 700 °C leads to precise control over the degree of condensation{,} and thus atomic construction and porosity of the resulting C2N-type materials. Depending on the condensation temperature of HAT-CN{,} nitrogen contents of more than 30 at% can be reached. In general{,} these carbons show adsorption properties which are comparable to those known for zeolites but their pore size can be adjusted over a wider range. At condensation temperatures of 525 °C and below{,} the uptake of nitrogen gas remains negligible due to size exclusion{,} but the internal pores are large and polarizing enough that CO2 can still adsorb on part of the internal surface. This leads to surprisingly high CO2 adsorption capacities and isosteric heat of adsorption of up to 52 kJ mol−1. Theoretical calculations show that this high binding enthalpy arises from collective stabilization effects from the nitrogen atoms in the C2N layers surrounding the carbon atom in the CO2 molecule and from the electron acceptor properties of the carbon atoms from C2N which are in close proximity to the oxygen atoms in CO2. A true CO2 molecular sieving effect is achieved for the first time in such a metal-free organic material with zeolite-like properties{,} showing an IAST CO2/N2 selectivity of up to 121 at 298 K and a N2/CO2 ratio of 90/10 without notable changes in the CO2 adsorption properities over 80 cycles.

Enhancement of the asymmetry in the hydrogen bond network of liquid water by an ultrafast electric field pulse - Elgabarty, Hossam; Kaliannan, Naveen Kumar; Kühne, Thomas D. (Scientific Reports)

Diffusion of Alkali Metals in Polycrystalline CuInSe2 and Their Role in the Passivation of Grain Boundaries - Chugh, Manjusha; Kühne, Thomas D.; Mirhosseini, Hossein (ACS Applied Materials & Interfaces)
The behavior of alkali atom point defects in polycrystalline CuInSe2 is studied. In this work, three grain boundary models, one coherent twin boundary and two twin boundaries with dislocation cores, are considered. Total energy calculations show that all alkali metals tend to segregate at the grain boundaries. In addition, the segregation of alkali atoms is more pronounced at the grain boundaries with the dislocation cores. The diffusion of alkali metals along and near grain boundaries is studied as well. The results show that the diffusion of alkali atoms in the grain boundary models is faster than within the bulk. In addition, the ion exchange between Na and Rb atoms at the grain boundaries leads to the Rb enrichment at the grain boundaries and the increase of the Na concentration in the bulk. While the effects of Na and Rb point defects on the electronic structure of the grain boundary with the anion-core dislocation are similar, Rb atoms passivate the grain boundary with the cation-core dislocation more effectively than Na. This can explain the further improvement of the solar cell performance after the RbF-postdeposition treatment.

Computing Bulk Phase Resonance Raman Spectra from ab initio Molecular Dynamics and Real-Time TDDFT - Brehm, Martin; Thomas, M. (J. Chem. Theory Comput.)

Triazolium-Based Ionic Liquids – A Novel Class of Cellulose Solvents - Brehm, Martin; Pulst, M.; Kressler, J.; Sebastiani, D. (J. Phys. Chem. B)

A General Algorithm to Calculate the Inverse Principal p-th Root of Symmetric Positive Definite Matrices - Richters, Dorothee; Lass, Michael; Walther, Andrea; Plessl, Christian; Kühne, Thomas (Communications in Computational Physics)
We address the general mathematical problem of computing the inverse p-th root of a given matrix in an efficient way. A new method to construct iteration functions that allow calculating arbitrary p-th roots and their inverses of symmetric positive definite matrices is presented. We show that the order of convergence is at least quadratic and that adaptively adjusting a parameter q always leads to an even faster convergence. In this way, a better performance than with previously known iteration schemes is achieved. The efficiency of the iterative functions is demonstrated for various matrices with different densities, condition numbers and spectral radii.

Using Approximate Computing for the Calculation of Inverse Matrix p-th Roots - Lass, Michael; Kühne, Thomas; Plessl, Christian (Embedded Systems Letters)
Approximate computing has shown to provide new ways to improve performance and power consumption of error-resilient applications. While many of these applications can be found in image processing, data classification or machine learning, we demonstrate its suitability to a problem from scientific computing. Utilizing the self-correcting behavior of iterative algorithms, we show that approximate computing can be applied to the calculation of inverse matrix p-th roots which are required in many applications in scientific computing. Results show great opportunities to reduce the computational effort and bandwidth required for the execution of the discussed algorithm, especially when targeting special accelerator hardware.

Theoretical Investigation of Interaction of CuInSe2 Absorber Material with Oxygen, Hydrogen, and Water - Sahoo, Sudhir; Kormath Madam Raghupathy, Ramya; Kühne, Thomas; Mirhosseini, Hossein (J. Phys. Chem. C)
We performed ab initio calculations to study oxygen and hydrogen point defects in the CuInSe2 (CISe) solar-cell material. We found that H interstitial defects (when one H atom is surrounded by four Se atoms) and HCu (when a H atom is replacing a Cu atom) are the most stable defects. Whereas these H substitutional defects remain neutral, H interstitial defects act as donor defects and are detrimental to the cell performance. The incorporation of H2 into the CISe lattice, on the other hand, is harmless to the p-type conductivity. Oxygen atoms tend to either substitute Se atoms in the CISe lattice or form interstitial defects, though the formation of substitutional defects is more favorable. All oxygen point defects have high formation energies, which results in a low concentration of these defects in CISe. However, the presence of oxygen in the system leads to the formation of secondary phases such as In2O3 and InCuO2. In addition to the point defects, we studied the adsorption of H2O molecules on a defect-free surface and a surface with a (2VCu + InCu) defect using the ab initio thermodynamics technique. Our results indicate that the dissociative water adsorption on the CISe surface is energetically unfavorable. Furthermore, in order to obtain a water-free surface, the surface with defects has to be calcined at a higher temperature compared to the defect-free surface.

Database screening of ternary chalcogenides for p-type transparent conductors - Kormath Madam Raghupathy, Ramya; Wiebeler, Hendrik; Kühne, Thomas; Felser, Claudia; Mirhosseini, Hossein (Chemistry of Materials)
In this work, we investigated ternary chalcogenide semiconductors to identify promising p-type transparent conducting materials (TCMs). High-throughput calculations were employed to find the compounds that satisfies our screening criteria. Our screening strategy was based on the size of band gaps, the values of hole effective masses, and p-type dopability. Our search led to the identification of seven promising compounds (IrSbS, Ba2GeSe4, Ba2SiSe4, Ba(BSe3)2, VCu3S4, NbCu3Se4, and CuBS2) as potential TCM candidates. In addition, branch point energy and optical absorption spectra calculations support our findings. Our results open a new direction for the design and development of p-type TCMs.

Impact of finite-temperature and condensed-phase effects on theoretical X-ray absorption spectra of transition metal complexes - Müller, Patrick; Karhan, Kristof; Krack, Matthias; Gerstmann, Uwe; Schmidt, Wolf Gero; Bauer, Matthias; Kühne, Thomas D. (Journal of Computational Chemistry)

Nanoscopic Structures and Molecular Interactions Leading to a Dystectic and two Eutectic Points in [EMIm][Cl] / Urea Mixtures - Cerajewski, U.; Träger, J.; Henkel, S.; Roos, A. H.; Brehm, Martin; Hinderberger, D. (Phys. Chem. Chem. Phys.)

Structure and Lifetimes in Ionic Liquids and their Mixtures - Gehrke, S.; von Domaros, M.; Clark, R.; Hollóczki, O.; Brehm, Martin; Welton, T.; Luzar, A.; Kirchner, B. (Faraday Discuss.)

Salt Bridge in Aqueous Solution: Strong Structural Motifs but Weak Enthalpic Effects - Pylaeva, S.; Brehm, Martin; Sebastiani, D. (Sci. Rep.)

An Efficient Lossless Compression Algorithm for Trajectories of Atom Positions and Volumetric Data - Brehm, Martin; Thomas, M. (J. Chem. Inf. Model.)